Seismic effect of industrial explosions of GOK Kostomuksha - Zueva I. A.; Lebedev A. A. (Vestnik MGTU, 2020)
Active development of quarries in the Republic of Karelia contributes to the improvement of the control system of the parameters of drilling and blasting operations with the aim of ensuring the safety of buildings and structures near mining facilities. During the study of the seismic effect of industrial explosions, the technology of blasting has been considered and a typical scheme of blasting at a mining enterprise has been described. In the quarries of the Kostomuksha mining and processing plant, to reduce the seismic effect, short-blasting is used. The created monitoring system in Karelia makes it possible to select not only teleseismic earthquakes, but also regional and local scale events on the seismic records. Explosions are recorded by seismic stations of the Karelian network and other regions if the magnitude of the event is more than 1.7. As a result of the waveforms' analysis of the records of the seismic station KOS6, located a few kilometers from the quarries, a clear entry of the transverse wave has been noted. The values of the local magnitudes of the explosions established during the six months of 2018 vary from 1.5 to 2.5 and do not exceed 3. The constructed averaging line shows the dependence of magnitude on the total charge; facts of its growth are noted with an increase in the total mass of the charge, as well as significant spread of data from the averaging line. In the course of the study, the possibility of reducing the seismic effects of industrial explosions through the use of effective short-delayed invocation schemes has been determined.